EVALUATION OF THE SPEED OF RESPONSE OF PRIMARY HEALTH CARE WORKERS IN HANDLING PATIENTS WITH HYPERTENSION CRISIS - Aritonang, Barita (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
Hypertensive crisis is an emergency condition that requires rapid treatment to prevent complications such as heart failure, stroke, or other organ damage. The speed of response of health workers in primary care is a crucial factor in handling this condition. The purpose of this study was to evaluate the speed of response of health workers in handling patients with hypertensive crisis and to identify the factors that influence it. Research methods: Quantitative and qualitative approaches. Quantitative data were obtained from patient medical records, while qualitative data were collected through interviews with health workers in primary care facilities. The parameters measured included initial assessment time, diagnosis time, treatment initiation time, and referral time if needed. The results showed that the average initial assessment time was 8 minutes (ideal ?5 minutes), diagnosis time 15 minutes (ideal ?10 minutes), treatment initiation time 12 minutes (ideal ?10 minutes), and referral time 25 minutes (ideal ?20 minutes). Several stages of treatment are still delayed due to limited medical personnel, lack of training, and suboptimal referral systems and standard protocols. Discussion: shows that health workers need further training in recognizing and handling hypertensive crises effectively. Optimizing the triage system and improving referral coordination are also important factors in accelerating treatment. Conclusion: although several aspects of service are quite good, improvements are still needed in the primary health care system so that patients with hypertensive crises receive faster and more appropriate treatment, thereby reducing the risk of complications and mortality.